2003
DOI: 10.1128/jcm.41.12.5732-5734.2003
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Two Miniaturized Systems, MicroScan W/A and BBL Crystal E/NF, for Identification of Clinical Isolates of Aeromonas spp

Abstract: Fifty-two clinical strains and 22 type and reference Aeromonas strains, previously genetically characterized by 16S rRNA gene restriction fragment length polymorphism, were identified in parallel with the MicroScan Walk/Away and BBL Crystal Enteric/Nonfermenter systems. The former identified only 14.8% of the isolates correctly, and the latter identified only 20.3% correctly, which indicates that neither of these systems is useful for this purpose.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
32
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 21 publications
6
32
0
Order By: Relevance
“…These strains were verified up to species level as A. hydrophila, A. sobria, and A. hydrophila/caviae using the API 20E system (Table 1) which in line with report by, Soler et al, 2003;Ormen et al, 2005).…”
Section: Morphological and Biochemical Characterizationsupporting
confidence: 51%
“…These strains were verified up to species level as A. hydrophila, A. sobria, and A. hydrophila/caviae using the API 20E system (Table 1) which in line with report by, Soler et al, 2003;Ormen et al, 2005).…”
Section: Morphological and Biochemical Characterizationsupporting
confidence: 51%
“…Considering only the 86 Aeromonas strains isolated from diseased fish, the species recognised by biochemical identification methods were: (Beaz-Hidalgo et al, 2009;. This study clearly highlighted once more that there was a false importance attributed to the species A. hydrophila as the most prevalent (Beaz-Hidalgo et al, 2010;Figueras, 2005;Figueras et al, 2011b;Soler et al, 2003b). Regarding A. salmonicida,85.7% (12/14) of the strains that showed to be psycrophilic, non motile and pigment producers had been correctly identified.…”
Section: Discrepancies Between Biochemical and Molecular Identificatimentioning
confidence: 71%
“…The mentioned systems normally tend to identify all Aeromonas strains as A. hydrophila (Figueras, 2005;Soler et al, 2003b). Some other authors have also reported poor results from the API systems and discrepancies with traditional tube testing when identifying Aeromonas strains isolated from fish (Godoy et al, 2010;Han et al, 2011;Joseph & Carnahan, 1994;and references therein).…”
Section: Phenotypic Identification With Conventional Methods and Minimentioning
confidence: 99%
See 1 more Smart Citation
“…The genus belongs to the family Aeromonadaceae, order Aeromonadales, class Gammaproteobacteria The taxonomy of this genus is complex because, despite each species apparently having specific phenotypic characteristics, biochemical identification is laborious and very imprecise, showing poor correlation with genotypic identification (Borrell et al, 1998;Soler et al, 2003;Figueras, 2005;Ormen et al, 2005). The 16S rRNA gene sequence similarity among species of the genus is very high, ranging from 96.7 to 100 % (Martínez-Murcia et al, 1992Saavedra et al, 2006).…”
mentioning
confidence: 99%